Synthesis and biological evaluation of cytotoxic analogs of somatostatin containing doxorubicin or its intensely potent derivative, 2-pyrrolinodoxorubicin - Nagy, Attila (The National Academy of Sciences, 1998)
To create cytotoxic hybrid analogs of somatostatin (SST), octapeptides RC-160 (d-Phe-C [Formula: see text] s-Trp-NH(2)) and RC-121 (d-Phe-C [Formula: see text] s-Thr-NH(2)) were linked to doxorubicin (DOX) or its superactive derivative, 2-pyrrolino-DOX (AN-201). The conjugation was performed by coupling N-9-fluorenylmethoxycarbonyl (N-Fmoc)-DOX-14-O-hemiglutarate or 2-pyrrolino-DOX-14-O-hemiglutarate to the amino terminus of [Lys(Fmoc)(5)]RC-160 yielding AN-163 and AN-258, respectively, after deprotection. The respective cytotoxic conjugates of RC-121 (AN-162 and AN-238) were prepared similarly. In vitro tests on human cancer cell lines—MKN-45 gastric cancer, MDA-MB-231 breast cancer, PC-3 prostate cancer, and MIA PaCa-2 pancreatic cancer—demonstrated that the antiproliferative activity of the cytotoxic radicals in these conjugates was virtually retained. In H-345 human small cell lung carcinoma cell line, conjugates of RC-121 preserved the cytotoxic activity of their radicals, but the hybrids with RC-160 showed ≈10 times lower activity. The ability of the carriers and the hybrids to inhibit the binding of (125)I-labeled RC-160 to receptors for SST on rat pituitary membrane preparation was also determined. The cytotoxic conjugates inhibited 50% of the specific binding of the radioligand in the nanomolar concentration range (IC(50) < 80 nM). When SST-like activities of AN-238 and its carrier, RC-121, were compared in the rat pituitary superfusion system, both compounds were found to suppress a stimulated growth hormone release at nanomolar concentrations. Preliminary studies in animal models of breast and prostate cancers showed that AN-238 is less toxic than AN-201 and more potent in inhibiting tumor growth. These highly active cytotoxic analogs of SST have been designed as targeted antitumor agents for the treatment of various cancers expressing receptors for SST octapeptides.